Analisis Hukum Terhadap Kasus Tindak Pidana Aborsi (Studi Putusan: No. 118/ Pid.Sus/2014/ Pn.Kng) - Harahap, Hariro (Iuris Studia: Jurnal Kajian Hukum, 2020)
Abortion is seen as a negative thing. The absence of the government's role in the process of counseling about the dangers of abortion, both to medical personnel, and to the community, especially families, is evident in various cases and incidents that often occur. Due to the absence of counseling to various parties, many victims of abortion perpetrators have had their pregnancies terminated (abortions) secretly, most of whom are assisted by untrained personnel. The problems in this research are; How is the legal arrangement for the criminal act of abortion in criminal law, how is the analysis of criminal law in the criminal case of abortion in decision Number 118 / Pid.Sus / 2014 / PN.KNG, what are the juridical obstacles in the process of enforcing criminal law against the criminal case of abortion. Based on the results of the research, it is understood that the Criminal Code Book becomes a book or reference for taking action against perpetrators of criminal abortion and that becomes a legal rule in particular is Law Number 36 of 2009 concerning Health, and added with Government Regulations as a complement to the legal rules regulates the crime of abortion, namely (PP) Number 61 of 2014 concerning Reproductive Health. Penal law enforcement in the crime of abortion on the object of this research seems weak, so that the legal objective of benefit is not achieved. The actions carried out by the defendant in the verdict of case Number 118 / Pid-Sus / 2014 / PN.KNG, constituted an act of abortion provokatus. Obstacles that are found in the enforcement of abortion criminal cases include the weak legal sanctions in this crime.